Factors That Influence Share Prices In The Food And Beverages Subsector Listed On IDX 2021-2024 - Aisyah Wulandari Marbun; Maliki Heru Santosa; Khoirun Nuranisa Safitri (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2025)
Purpose – This study aims to determine the effect of Profitability, Good Corporate Governance, Corporate Social Responsibility and Leverage on Share Price. Design/methodology/approach – This research uses quantitative data, the sample in this study is subsector food and beverages which are listed on Indonesia Stock Exchange in the period 2021-2024 as many as 40 companies selected through purposive sampling method. The analysis technique used is multiple linear regression analysis with E-views 9 as software. Findings – The results of this study indicate that the Profitability variable is not significant on Share Price, Good Corporate Governance is not significant on Share Price, Corporate Social Responsibility is significant on Share Price and Leverage is not significant on Share Price Research limitations/implications – This study only has several limitations that should be considered when interpreting the result. Sample size is limited to the subsector food and beverages and this research year only during 2021-2024